Toward an ethically committed linguistics (Revista de Estudos da Linguagem, 1999)
The pivotal claim of this paper is that ethical issues are invariablypresent in Linguistics even at those moments when one is discussingwhat are presumably ‘purely theoretical’ problems. The reason whymany linguists have difficulty in recognising this is that they areencumbered by a host of dogmas in relation to how a scientificarea of study is constituted. Among these dogmas is the idea thatthe raw materials of the science of language are the so-called ‘hardfacts’ – entities that are, by definition, devoid of any ultimateinterests. It is further believed that all that Linguistics attempts todo is to describe them, or, following Chomsky’s recommendation,explain the whys and wherefores of things, but always in waysthat are purely internal to the phenomena in question.